OP0265 Mortality after fragility hip fracture in middle aged and elderly men and women in southern norway. (23rd January 2014) - Diamantopoulos, A.P.; Hoff, M.; Hochberg, M.; Haugeberg, G.
Abstract : Background: The mortality in patients with fragility hip fracture is higher compared to the general population for both men and women (1). The highest incidence of fragility hip fracture has been reported from Norway and other Scandinavian countries (2). Updated mortality data in patients with hip fracture is limited, in particular for long-term survival. Objectives: Our aim was to study the overall mortality rates of fragility hip fracture in men and women in Southern Norway after 1 and 5 years compared with the mortality rates of the Norwegian population. Methods: Individuals over 50 years (residents of the two southern counties of Norway) with a fragility hip fracture between 1 January 2004 and 31 December 2005 were identified by using the hospital electronic diagnosis registers coded as S72.0-2 (ICD-10). The follow-up time for one person was from the month the fracture occurred to death or the censoring date in January 1, 2009 and 2010. To calculate the standardized mortality ratio (SMR), the mortality risk of the standard Norwegian population was used (3). Statistical significance was defined as p<0.05. Results: The final number of fragility hip fractures in the geographic area of Southern Norway was 951 (271 men and 680 women). Mean age for all included patients was 81.2 years (men 80.0 years and women 81.8 years). After one year the overall mortality rate was 22.7% (men 32.1%, women 19.0%, p<0.005) and after 5 years 58.5% (men 69.9%, women 54.3%, p<0.005). The overall mortality rate for hip fracture patients older than 80 years after one year was 29.4% (men 44.6%, women 24.0%, p<0.005) and after five years 69.2% (men 85.4%, women 63.5%, p<0.005). The SMR for the men and women compared to the Norwegian population for the first year was 2.08 (95% CI 1.77-2.38) and 2.78 (95% CI 2.24-3.31) and after five years 1.82 (95% CI 1.41-2.22) and 3.10 (95% CI 2.21-3.98). Conclusions: Mortality in fragility hip fracture patients is elevated compared to the background population during the first year and remains elevated also after five years. Mortality rates after a fragility hip fracture was higher in men than women. One explanation may be the lower life expectancy in men than in women. References: Vestergaard P, Rejnmark L, Mosekilde L. Increased mortality in patients with a hip fracture-effect of pre-morbid conditions and post-fracture complications. Osteoporos Int. 2007 Dec;18(12):1583-93. Diamantopoulos AP, Rohde G, Johnsrud I, Skoie IM, Johnsen V, Hochberg M, et al. Incidence rates of fragility hip fracture in middle-aged and elderly men and women in southern Norway. Age Ageing. 2011 Sep 6. Statistics, Norway. Aldersavhengige dødsfallsrater for menn og kvinner. 1971-2010 (Age-related mortality rates for men and women, 1970-2010). Available from: http://www.ssb.no/dode/tab-2011-04-14-02.html . Disclosure of Interest: None Declared